Pengaruh Foreign Direct Investment Terhadap Stabilitas Nilai Tukar Rupiah dalam Pertumbuhan Perekonomian di Indonesia - Julia Ameliani; Irvan Yoga Pardistya; Liya Megawati (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the relationship between Foreign Direct Investment (FDI) and the stability of the Indonesian rupiah exchange rate within the broader context of Indonesia’s economic environment. Given the strategic role of FDI in stimulating economic activity, fluctuations in foreign investment inflows are often accompanied by changes in the exchange rate, which in turn affect monetary stability. The research employs a quantitative approach using simple linear regression, supported by secondary data from 2019-2024 obtained from official institutions and relevant scholarly sources. The results indicate that FDI has a significant influence on the rupiah exchange rate, as evidenced by highly significant values in both t-test and F-test. Although the data distribution is not fully normal, the consistency of the statistical findings reinforces the interpretation that FDI contributes to movements in the exchange rate. Therefore, this study concludes that increasing foreign investment not only enhances economic capacity but also plays a role in shaping the medium-term stability of the Indonesian rupiah.